The simplified forms of the given expressions are
a. 32x
b. 0
c. -26t + 14x
d. 3t
<h3>Simplifying an expression </h3>
From the question, we are to simplify the given expressions by adding or subtracting
a. (10x) + (22x)
= 32x
b. (-6x) - (-6x)
= -6x + 6x
= 0
c. (-13t) + (14x) - (+13t)
= -13t + 14x - 13t
Collect like terms
= -13t -13t + 14x
= -26t + 14x
d. (-4t) + (+4t) - (-3t)
= -4t + 4t + 3t
= 3t
Hence, the simplified forms of the given expressions are
a. 32x
b. 0
c. -26t + 14x
d. 3t
Learn more on Simplifying an expression here: brainly.com/question/723406
#SPJ1
Answer: z=16
Step-by-step explanation:
Angles on a straight line add up to 180.
As AB is a straight line we can use that to help us find z.
So you would do 68+85+11=164 (I got the 11 from the angle trapped between like C and F as opposite angles are the same).
Then you would do 180-164=16
So z=16
Hope this helps :)
Answer:
-199
Step-by-step explanation:
- put -6 in place of x in equation
Answer:
it would be b
Step-by-step explanation: